Factor influencing customer online purchase intention in cosmetic products / Nur Shafiqa Muhammad Marzuki - Muhammad Marzuki, Nur Shafiqa (Faculty of Business and Management, 2019)
The purpose of this research is to examine the factors influencing online purchase intention on cosmetic product among online consumers in Malaysia. One of the aims of this study is to know the main factors that influencing online purchase intention on cosmetic product as previous research only focused on conventional rather than e-business. This study is to observe the factors that influence relationship between the factors which are trust, perceived risk, shopping enjoyment, site design and online purchase intention as well as establish the significance of each factor in predicting online purchase intention on cosmetic product. Online questionnaires were distributed to the respondents from Melaka Tengah. Through the online questionnaires, the Statistical Programme for Social Sciences (SPSS) was used to analysis the data. Analyses were done to achieve the objectives of this study which are to determine the relationship between trust, perceived risk, shopping enjoyment and site design with online purchase intention and to identify the most influential factor towards online purchase intention. Lastly, the researcher hopes that this study will help online retailers to be more aware on what are the factors that influence online purchase intention on cosmetic products.